2022
DOI: 10.1155/2022/5061112
|View full text |Cite|
|
Sign up to set email alerts
|

Multidimensional CNN-Based Deep Segmentation Method for Tumor Identification

Abstract: Weighted MR images of 421 patients with nasopharyngeal cancer were obtained at the head and neck level, and the tumors in the images were assessed by two expert doctors. 346 patients’ multimodal pictures and labels served as training sets, whereas the remaining 75 patients’ multimodal images and labels served as independent test sets. Convolutional neural network (CNN) for modal multidimensional information fusion and multimodal multidimensional information fusion (MMMDF) was used. The three models’ performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it could suggest value in having a time series ultrasound image input for improving image training as M-mode results outperformed all B-mode results. Other studies have utilized higher-order inputs to CNN models to include more contextual detail [39,40] or successfully integrate recurrent neural network architecture for better tracking time series details in ultrasound images [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could suggest value in having a time series ultrasound image input for improving image training as M-mode results outperformed all B-mode results. Other studies have utilized higher-order inputs to CNN models to include more contextual detail [39,40] or successfully integrate recurrent neural network architecture for better tracking time series details in ultrasound images [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A critical thinker is skilled at challenging presumptions, looking for different viewpoints, and drawing well-informed, independent judgements. (Martin et al, 2022) Critical thinking is a set of abilities and ways of thinking that help people solve issues, evaluate data, and come to well-informed conclusions. The following are some essential forms or elements of critical thinking:…”
Section: Critical Thinkingmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%